The Note on Morphology of Rafflesia hasseltii Surigar from Bukit Tiga Puluh National Park, Riau - NERY SOFIYANTI; KAMARUDIN MAT SALLEH; DEDEK PURWANTO; EDY SYAHPUTRA (Biodiversitas Journal of Biological Diversity, 2007)
The detail observation had been done on the morphological characters of Rafflesia hasseltii from Bukit Tiga Puluh National Park (BTNP). Currently, this endangered and rare flower found in two populations in this park, Aek Telap and Mandi Urau, Tanah Datar. The preliminary study on morphological characters of flowers from this site shows blotches and dot pattern variability. The detail observation of morphology of R. hasseltii from BTNP, presented the similarity to its type except the blotches pattern in perigone lobe. However, the further monitoring research is still needed to observe more flowers in this site. Due to its rarity, study on all Rafflesia species must be carefully done especially in using the characters of blotch for taxonomy evidence, as this characters show the variability among the flowers within population.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: Rafflesia hasseltii, tjendawan muka rimau, morphology